Evidence of spillover effect of direct competition between marketing cooperatives and private intermediaries in Thai rice value chains - CGIAR Research Program on Rice (2021)
We provided evidence of the spillover effect in Thailand, which can be used as a proof of concept to encourage development of policies that stimulate marketing cooperative movement in the rice sector in other South or Southeast Asian or in African countries.